Peningkatan Keterampilan Berbicara Bahasa Inggris Siswa melalui Metode Project-Based Learning pada Presentasi Teknis SMKN I Tapaktuan - Yulita Halim (CV. Rumoh Aceh Publishing, 2026)
This research aims to analyze the improvement of English speaking skills among students majoring in Computer and Network Engineering (TKJ) at SMKN I Tapaktuan through the implementation of Project-Based Learning (PjBL) method based on technical presentations. This study employed a qualitative approach using Classroom Action Research (PTK) method. Data were collected through classroom observations, video recordings of presentations, and in-depth interviews, which were linguistically analyzed to understand students' speech patterns and technical terminology usage. Data validity was ensured through trustworthiness principles encompassing credibility, transferability, dependability, and confirmability. The findings indicate that PjBL integrated with technical presentations significantly enhanced students' speaking abilities. Students demonstrated improvements in fluency, accuracy of technical vocabulary (technical jargon) usage, and confidence in communicating in English. This research concludes that the relevance of technical materials to English language practice serves as the primary key in overcoming communication barriers for students in vocational education settings.